Teaching patients about pain: It works, but what should we call it? - Louw, Adriaan; Puentedura, Emilio "Louie" J.; Zimney, Kory (Physiotherapy theory and practice, 2016)
It is now well established that people in pain, especially persistent pain, have a strong desire to know more about why they continue to hurt (Louw, Louw, and Crous, 2009). Using the traditional educational models, a clinician would likely teach a patient presenting with “shoulder pain” more about their shoulder, not about pain. Although such an anatomically driven educational model might have value for the patient with an acute or perioperative condition, it has been shown to be of little to no value in the case of persistent pain (Nijs et al., 2013). Pain is complex. We now understand that when scanned and tested, many people will have signs of pathology in their tissues (e.g., shoulder) with little to no pain, and conversely, many with normal scans and tests suffer from persistent pain (Spielmann et al., 1999).